Studying the role of bacteria in pine wilt disease development - Alves, Marta Salgueiro (2019)
Bursaphelenchus xylophilus (Nematoda: Aphelenchoididae) is considered an A2 quarantine pest in the European Union and the only recognized causative agent of the pine wilt disease (PWD), a disease affecting pine trees in Europe and Asia with far-reaching economic and environmental impacts. Tree to tree transmission of B. xylophilus depends on its insect-vector of the genus Monochamus (Cerambycidae: Coleoptera). Wilt toxins were found to be produced by nematode-associated bacteria leading to the hypothesis that bacteria might play an important role in the wilt mechanism. Similarly, the insect-vector and the host tree microbiome might be relevant for the disease mechanism. Therefore, the aim of this study is to clarify the role of bacteria in pine wilt disease through the characterization of the bacterial communities’ composition and function associated to the disease players: the nematode, the insect-vector and the tree. To do so, both culture-independent (denaturing gradient gel electrophoresis, massive parallel sequencing and clone libraries) and classic culture-dependent methods were used. Results demonstrated that the disease players (i.e. the nematode, the insectvector and the tree) each has a specific bacterial community, which is influenced by the environmental context. However, a core microbiome was identified, comprising shared bacterial groups mainly of the families Enterobacteriaceae and Pseudomonadaceae. When analysing insect-vectors from different species, the results demonstrated a species-specific microbiome. The bacterial community composition of the nematode in its propagative stage was similar to one from the insect vector, suggesting that it may, in part, be inherited from the insect. In agreement, the Pseudomonas community associated to the nematode and the insect-vector were similar and different from the one associated to the tree. Results showed that Pseudomonas might play a relevant role in disease progression. In silico analyses demonstrated the potential of bacteria associated with the nematode and the insect for xenobiotic degradation and also for tree weakening. It was also possible to establish a collection of endophytic bacterial isolates from trees belonging to three different pine species and to determine their traits regarding plant growth promotion, cell-wall degradation and oxidative stress tolerance. The results suggested the involvement of the pine endophytic community in tree susceptibility to B. xylophilus. The genome of four bacterial endophytic strains detected in the trees trunk were sequenced. From these, two Methylobacterium strains displayed genomic characteristics consistent with a positive interaction with the plant and gave a positive result in Arabidopsis thaliana root elongation assays, suggesting a potential to be used as biological control agents. Overall, this study demonstrated that the PWD results from a multitrophic interaction in which the microbiome associated to the disease is one of the players having a role in disease progression.